Assessment of Vitamin D Deficiency and its Possible Risk with Breast Cancer in Pakistan - Amir Iqbal Memon, Aisha Masroor Bhatti, Rizwan Khan, Nayab, Suhail Raza, Mohammed Qasim (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the vitamin D deficiency as a possible risk factor in breast cancer. Study design: Cross-sectional study Place and duration of study: Surgical Unit-II, Ward 5, Liaquat University of Medical & Health Sciences Jamshoro from 1stJanuary 2022 to 31st December 2022. Methodology: One hundred and twenty-seven patients with the complaints of lump/mass in the breast or nipple discharge ≥6-week duration and diagnosed as breast cancer regardless of stage/grade presented were enrolled. Results: 59.8% while the illiterate, primary, middle, secondary and higher were 36.2%, 14.2%, 17.3%, 20.5% and 11.8%. The statistical significance was observed for vitamin D deficiency in accordance with residence (p=0.03), duration of disease (p=0.05), educational status (p=0.05), hypertension (p=0.01), smoking (p=0.00), obesity (p=0.02), diabetes mellitus (p=0.04), raised CRP (p=0.00), hypocalcemia (p=0.00), ER/PR positive (p=0.01) and family history of breast cancer (p=0.04). Conclusion: Vitamin D deficiency is more prevalent in patients with breast cancer with rural population predominance. Keywords: Breast cancer, breast carcinoma, and vitamin D deficiency.